Pengaruh Brand Image dan Electronic Word of Mouth terhadap Keputusan Pembelian iPhone di Surabaya - Kartika Putri Pramesthi (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2025)
This study aims to analyze the influence of Brand Image (X1) and Electronic Word of Mouth (X2) on iPhone purchasing decisions in Surabaya. The rapid development of communication technology in Surabaya is reflected in the increasing number of smartphone users, who use them for communication, online shopping, and learning. A quantitative method was employed, with data collected through questionnaires distributed to 96 respondents using incidental sampling techniques. Instrument testing included validity and reliability tests, as well as classical assumption tests such as normality, multicollinearity, and heteroscedasticity. Data analysis was conducted using multiple linear regression through SPSS version 25. The results show that both Brand Image (X1) and Electronic Word of Mouth (X2) have a significant effect on iPhone purchasing decisions in Surabaya, both partially and simultaneously. These two variables contribute 40.1% to the purchasing decision, while the remaining 59.9% is influenced by other factors not examined in this study, such as lifestyle, product quality, and product design. Future research is recommended to expand on these findings by exploring additional variables and using different populations and samples